PROSTITUSI ONLINE ANAK DIBAWAH UMUR MELALUI APLIKASI MICHAT (Studi Kasus Terhadap 5 Anak Inisial NM, NS, TI, ST, IC) - Pujiastuti, Wahyulia; Munir , Abdul (Sisi Lain Realita, 2024)
The phenomenon of prostitution can be said as a crime, where that prostitutiom was activities and action who violates the regulations and norm that apply in the community are include deviant acts. Now in digital era this act develop, be it in terms of actors or practice. Like what happened on Pekanbaru city there is online prostitutipn carried out by minors with michat application. This research do with qualitative and descriptive method meaning to desribe and solve problem this research, with rational choice theory whic causes minors to become actor of prostitution was a based on that choice and fullfilling of life.